Love's enduring promise - Oke, Janette, 1935- (Oke, Janette, 1935- Love comes softly series, 2003)
In this sequel to Love Comes Softly, Clark and Marty Davis now preside over a growing family in their little prairie house. But as they reach out to those in their frontier community, they discover that love is not limited by the size of a dwelling.